The exploration of professionalism understanding of accounting educators? - Melinda Ibrahim; Unti Ludigdo; Gugus Irianto (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study aimed to explore professionalism understanding of accounting educators’ perspective. Professionalism is an implementable concept as a basic of self quality development in each profession. This study was conducted at Universitas Lestari, one of the private universities in the Province of Gorontalo. The paradigm employed in this study is the interpretative paradigm in which Husserl’s Transcendental Phenomenology is applied to the approach. Based on the result of the study, there are three dimensions of professionalism found, namely professionalism as academic responsibility, professionalism as social responsibility, and professionalism as spiritual responsibility. Professionalism as academic responsibility is the initial dimension which is seen in the implementation of three services of university, the balance of rights and obligations, the observance of rules, and commitments. Professionalism as social responsibility is the second dimension which is committed in the trust and exemplary attitudes. Professionalism as spiritual responsibility is the highest dimension materialized in the faith in which work is considered as worship.